A study of warpage and weld line defects on a plastic composite's manhole cover - Hazwani Kamarulzzaman (School of Manufacturing Engineering, University Malaysia Perlis, 2010)
This study is about choosing and identifying the most suitable plastic composites material which can best replaced cast iron The plastics composites must be high durability and low cost.